Reconciling market and moral logics on a minimum wage: Supermarket work in Australia during the first two years of the SARS-COV-2 pandemic - Chris Degeling; Sittichoke Chawraingern; Gwendolyn L. Gilbert; Claire Hooker; Su-yin Hor; Jane Williams (SSM: Qualitative Research in Health)
Essential workers generate and maintain basic services that populations must receive, without interruption, to sustain a healthy, functional society. When SARS-COV-2 spread around the world, mundane low-paid work in essential non-healthcare industries such as supermarkets, became high risk, makeshift and unpredictable. Drawing on recent scholarship in the sociology of work, we conducted 32 interviews to capture how supermarket workers in Australia navigated the trade-offs and moral choices entailed in performing essential roles in non-health settings during a pandemic. We found that, as key assumptions about the resilience of globalised modernity and its supporting systems were tested, supermarket workers found themselves at the centre of experiments and public debates about the effectiveness and appropriateness of different infection control measures. Compensating for a lack of preparedness by governments and corporations, they were forced to accept, and then tasked with resolving inconsistencies between the political economy of low paid work and the moral economy of social provision. Given the experiences of those who found themselves in essential roles outside healthcare, there is an urgent need to reconceptualize what ‘successful’ pandemic preparedness and response entails. Reflecting on their experiences, these workers told us that expressions of solidarity and concern, from those not sharing their position of biological and financial precarity, were of little value. Drawing on the market logics that define their employment as essential and replaceable, the workers we spoke to observed that fair renumeration for risks and better protections were the most important considerations in recasting how societies prepare for future pandemics.